Non-Equilibrium Statistical Mechanics - Luscombe, James H. (Boca Raton : CRC Press/Taylor & Francis Group, 2025)
This book is a companion or follow-on volume to Statistical Mechanics by the same author. As with Statistical Mechanics (which covers the equilibrium aspects of the subject), this book provides a beautifully written, accessible yet very thorough coverage of the topics, building on the author's many years of teaching experience. Covering a broad range of advanced, extension topics, it can be used to support advanced courses, or as a supplementary text for core courses in this field. Those teaching courses (as well as those researching in the area) will also find the book to be an invaluable reference. Modern applications of the subject (in physics and related areas) are included throughout.
Includes bibliography and index.
Keywords: Nonequilibrium statistical mechanics; Fluctuations; Irreversible processes; Gaussian Processes